求微分方程y^2dx+(x^2-xy)dy=0 的通解

2024-11-23 01:45:29
推荐回答(3个)
回答1:

解:∵(3xy+x^2)dy+(y^2+xy)dx=0==>2y(3xy+x^2)dy+2y(y^2+xy)dx=0(等式两端同乘2y)==>2(3xy^2dy+y^3dx)+2(x^2ydy+xy^2dx)=0==>2d(xy^3)+d(x^2y^2)=0==>2∫d(xy^3)+∫d(x^2y^2)=0==>2xy^3+x^2y^2=C(C是常数)∴此方程的通解是2xy^3+x^2y^2=C。

回答2:

整理有
dy/dx=y^2/(xy-x^2)=(y/x)^2/[(y/x)-1]
令y/x=u,y=ux,y'=u+xu'
则原微分方程可化为
u+xu'=u^2/(u-1)
xu'=u/(u-1)
(u-1)/udu=1/xdx
两边积分
u-ln|u|=ln|x|+C
通解为
(y/x)+ln|y/x|=ln|x|+C
即(y/x)+ln|y/x^2|=C

回答3:

齐次方程
令y=tx,dy=tdx+xdt带入:
t^2x^2dx+(x^2-tx^2)(tdx+xdt)
tdx+(1-t)xdt=0
dx/x=(1-1/t)dt
ln|x|=t-ln|t|+C1
ln|x|+ln|t|=t+C1
ln|y|=y/x+C1
y=Ce^(y/x)